LIFESTYLE ON INTENTION THROUGH THE MEDIATION OF PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE - Juniati Juniati; Indarini Indarini (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2013)
This study aims to identify relevant lifestyle factors that affect consumer adoption of mobilephone (BlackBerry). Furthermore, this study attempts to examine the impact of lifestyle factorson perception and adoption of BlackBerry consumers. Using the technology acceptance model asa theoretical framework, the conceptual model depicts the relationships among lifestyles,perceptions, and intention. Two-step structural equation modeling was used to test the proposedhypotheses. Results of this study show that consumer lifestyle factors (fashion consciousness,Internet involvement, and e-shopping preference) are direct and indirect antecedents ofconsumers’ intention to adopt BlackBerry phone. Findings of this study provide marketers withinsights into how knowledge about lifestyle factors can be integrated into marketing andadvertising strategies.Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor gaya hidup yang mempengaruhiminat mengadopsi telepon selular (BlackBerry). Selain itu, penelitian ini bertujuan untukmenguji pengaruh faktor gaya hidup terhadap persepsi dan minat mengadopsi telepon selularBlackBerry. Studi ini menggunakan model penerimaan teknologi sebagai kerangka teori, modelkonseptual menggambarkan hubungan antara gaya hidup, persepsi, dan niat. Untuk mengujihipotesis yang diajukan digunakan pemodelan persamaan struktural. Hasil dari penelitian inimenunjukkan bahwa faktor gaya hidup konsumen (kesadaran fashion , keterlibatan internet, danpreferensi e-shopping) adalah anteseden langsung dan tidak langsung dari niat konsumen untukmengadopsi telepon selular BlackBerry. Temuan penelitian ini memberi pemasar wawasanmengenai bagaimana pengetahuan tentang faktor gaya hidup dapat diintegrasikan ke dalamstrategi pemasaran dan periklanan.